Excel Programming with VBA Starter - Martin, Robert (Packt Pub., 2012)
Get started with programming in Excel using Visual Basic for Applications (VBA).
Print version record
Keywords: Microsoft Visual Basic for applications; Microsoft Excel (Computer file)